(3eUMa TQjas
(3ChdgG (B:s
(3GdLRA GdQGHY df JfGdh GdHQMJi JfabhG eeG JMHhf heG JfabhG ef TF aEf Gddg Hg Ydje s
(3BNQgG (B:s
(3GdPjf ef CUdGHce hCf JLeYhG Hjf GdCNJjf EdG eG bO Sda Ef Gddg cGf ZahQkG QMjekG s
(3GdLRA GdQGHY ef GdbQBf GdcQjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(153) s
Keywords: (3GdcJH GdSeGhjIs